Canine rangeliosis: The need for differential diagnosis - Da Silva A.S.* (2013)
Rangeliosis is a hemoparasitosis that affects dogs in Brazil. The disease has similar clinical and pathological characteristics to other hemo-protozoan infections. So, this paper has aimed to report a clinical case of infection by Rangelia vitalii in one dog, focusing on the need for the differential diagnosis to other infectious diseases. The animal showed apathy, anemia, thrombocytopenia, alteration of leucogram, and bleeding. The first difference was the observation of parasites in blood smears, where R. vitalii was visualized within leukocytes and erythrocytes. The confirmation of the clinical diagnosis was made by molecular test to R. vitalii. The dog was debilitated, and died a few hours after treatment at the veterinary hospital. At necropsy, splenomegaly, lymphadenopathy, and mild jaundice in the abdominal viscera were found. This article draws attention to the need for the parasitological, serological, and molecular to differential diagnosis in order to differentiate from other clinically similar disorders. © 2012 Springer-Verlag Berlin Heidelberg.